Urbanism as craft: Practicing informality and property in Cairo’s gated suburbs, from theft to virtue - Simcik-Arese, N (Taylor and Francis, 2017)
For many people and institutions in Egypt, the messy appearance of informal settlements codes for its inhabitants' supposed immorality and thus illegality. Little is known, however, about how the subjects of such accusations interpret the relationship among built form, morality, and legality in so-called formal urbanism. When a group of urban poor from central Cairo is resettled into Haram City, a private development subsidized by the state as “affordable housing” but operating as a budget gated community, disemployment and the developer's hypocrisy provoke them to occupy vacant homes and gardens. As the squatters modify properties to create jobs, and as middle-class homeowners disparage them, the squatters appropriate “informality” to articulate their own vernacular position on the immorality of formal planning. This ethnography shows how squatters develop a notion that the just city binds morality and economy together when buildings manifest labor relations: people and places that are “practiced” (mugarrab, also experienced or tested) as virtuous. It then shows how squatters instrumentalize this concept as informal expertise to persuade formal city staff, managers, and homeowners of squatters' legitimacy: They demonstrate divisibility within property rights to protect productive urbanism's use value and challenge speculative urbanism's exchange value. To this end, I introduce two literatures rarely applied to southern urbanism: the “moral economy” as an innovative lens for geographers exploring embedded economies (Thompson 1991) and legal geography critiquing a “single owner model” of ownership (Singer 2000a).